Of Sunken Islands and Pestilence Restoring the Voice of Edward Taylor Fletcher to Nineteenth-Century Canadian Literature - Fletcher, Edward Taylor (Athabasca University Press, 2022)
Edward Taylor Fletcher was born in England in 1817 and arrived in Canada as a young boy. An important figure in Canadian literature, Fletcher's writing was almost entirely forgotten by history. In this volume, James Gifford has gathered and annotated Fletcher's essays and poems, writings that describe a nineteenth-century Canadian cultural life far more cosmopolitan than what we might have imagined. Fletcher was a voracious reader of works in many languages and although he was oriented toward Britain, his writing notably reflects a gaze fixed on a horizon much further away. His work therefore stands in contrast to the tendency of later Canadian writers, who focus inward on the nation, and on issues of Canadian identity. His work as a surveyor allowed him to travel across the country, observing the Canadian landscape which appears interwoven with different literary traditions in his metrically complex poetry. By recuperating Fletcher's works, Gifford expands our view of nineteenth-century Canadian literature and establishes Fletcher as a remarkable literary figure worthy of attention.